Aldehyde dehydrogenase 2 deficiency ameliorates alcoholic fatty liver but worsens liver inflammation and fibrosis in mice. Issue 1 (28th May 2014) - Kwon, Hyo‐Jung; Won, Young‐Suk; Park, Ogyi; Chang, Binxia; Duryee, Michael J.; Thiele, Geoffrey E.; Matsumoto, Akiko; Singh, Surendra; Abdelmegeed, Mohamed A.; Song, Byoung‐Joon; Kawamoto, Toshihiro; Vasiliou, Vasilis; et al.
<x xml:space="preserve">Abstract</x> Aldehyde dehydrogenase 2 (ALDH2) is the major enzyme that metabolizes acetaldehyde produced from alcohol metabolism. Approximately 40‐50% of East Asians carry an inactive ALDH2 gene and exhibit acetaldehyde accumulation after alcohol consumption. However, the role of ALDH2 deficiency in the pathogenesis of alcoholic liver injury remains obscure. In the present study, wild‐type and ALDH2−/− mice were subjected to ethanol feeding and/or carbon tetrachloride (CCl4) treatment, and liver injury was assessed. Compared with wild‐type mice, ethanol‐fed ALDH2−/− mice had higher levels of malondialdehyde‐acetaldehyde (MAA) adduct and greater hepatic inflammation, with higher hepatic interleukin (IL)‐6 expression but surprisingly lower levels of steatosis and serum alanine aminotransferase (ALT). Higher IL‐6 levels were also detected in ethanol‐treated precision‐cut liver slices from ALDH2−/− mice and in Kupffer cells isolated from ethanol‐fed ALDH2−/− mice than those levels in wild‐type mice. In vitro incubation with MAA enhanced the lipopolysaccharide (LPS)‐mediated stimulation of IL‐6 production in Kupffer cells. In agreement with these findings, hepatic activation of the major IL‐6 downstream signaling molecule signal transducer and activator of transcription 3 (STAT3) was higher in ethanol‐fed ALDH2−/− mice than in wild‐type mice. An additional deletion of hepatic STAT3 increased steatosis and hepatocellular damage in ALDH2−/− mice. Finally, ethanol‐fed ALDH2−/− mice were more prone to CCl4‐induced liver inflammation and fibrosis than ethanol‐fed wild‐type mice. Conclusion: ALDH2−/− mice are resistant to ethanol‐induced steatosis but prone to inflammation and fibrosis by way of MAA‐mediated paracrine activation of IL‐6 in Kupffer cells. These findings suggest that alcohol, by way of acetaldehyde and its associated adducts, stimulates hepatic inflammation and fibrosis independent from causing hepatocyte death, and that ALDH2‐deficient individuals may be resistant to steatosis and blood ALT elevation, but are prone to liver inflammation and fibrosis following alcohol consumption. (Hepatology 2014;60:146–157)